Analisis Rasio Keuangan Untuk Memprediksi Kondisi Financial Distress Perusahaan Manufaktur - Deny Liana; - Sutrisno (Trunojoyo University of Madura, 2014)
The purpose of this study was to examine the effect of financial ratios to predict financial distress on manufacturing company in the Indonesian Stock Exchange. In this study the financial ratios variable is proxied by liquidity, profitability (NPM), financial leverage, and growth as independent variables. While financial distress as measured by the Z-score as the dependent variable.The population in this study were all the manufacturing companies that listed on the Indonesian stock exchange. Samples are taken of eighty-one manufacturing company with purposive sampling method, and observation period during three years (2009-2011).The results showed that liquidity has a negative effect but not significant to the financial distress. Profitability (NPM) has a significant and positive effect on financial distress, while financial leverage and growth have unsignificant but positive effect on financial distress.